Peningkatan Hasil Belajar Peserta Didik pada Pembelajaran Tematik Terpadu Menggunakan Model Flipped Classroom di Kelas V SDN 176/Iv Kota Jambi - Fadhilla, Khairana; Reinita, Reinita (MODELING: Jurnal Program Studi PGMI, 2023)
This research purpose to improve student learning outcomes in thematic learning using Flipped Classroom model in class V SDN 176/IV JAMBI CITY. This research is Classroom Action Research, subjects in this study are teachers and students of grade V there are 8 male students and 8 female students. The results showed an increase, : a) the results of RPP observations in first cycle 81%, in second cycle 97%. b) the results of teacher activity in first cycle are 78.5%, in second cycle 93%. c) the results of student activity in first cycle are 78.5%, in second cycle 93%.